Security of Internet of Things Nodes : Challenges, Attacks, and Countermeasures. - Chakraborty, Chinmay, 1984-; Rajendran, Sree Ranjani; Rehman, Muhammad Habibur ([Place of publication not identified] : Chapman and Hall/CRC, 2021)
The book Security of Internet of Things Nodes: Challenges, Attacks, and Countermeasures® covers a wide range of research topics on the security of the Internet of Things nodes along with the latest research development in the domain of Internet of Things. It also covers various algorithms, techniques, and schemes in the field of computer science with state-of-the-art tools and technologies. This book mainly focuses on the security challenges of the Internet of Things devices and the countermeasures to overcome security vulnerabilities. Also, it highlights trust management issues on the Internet of Things nodes to build secured Internet of Things systems. The book also covers the necessity of a system model for the Internet of Things devices to ensure security at the hardware level.
Securing Dedicated DSP Co-processors (Hardware IP) using Structural Obfuscation for IoT-oriented Platforms. Multi-bit True Random Number Generator for IoT devices using Memristor. Secured Testing of AES Cryptographic ICs for IoT Devices. Biometric-based Secure Authentication for IoT Enabled Devices and Applications. An improved verification scheme based on user biometrics. Obfuscation to Mitigate Hardware Attacks in the Edge Nodes of IoT System. Lightweight Security solutions for IoT using Physical Layer Key Generation. Threat and attack models in IoT devices. Review on Hardware attacks and security challenges in IoT Edge nodes. Study of Hardware attacks on Smart System Design Lab. A Novel Threat Modelling and Attack Analysis for IoT Applications. Trust management in Internet of Things devices
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Database Management / Data Mining; COMPUTERS / Computer Engineering; Internet of things -- Security measures